2022
DOI: 10.1111/cdev.13868
|View full text |Cite
|
Sign up to set email alerts
|

Changes in children’s anger, sadness, and persistence across blocked goals: Implications for self‐regulation

Abstract: The current study took a person‐centered approach to examine the heterogeneity of changes in children’s emotions and persistence during a goal‐blocking task and examined how different profiles of emotions and persistence related to children’s self‐regulation. Children’s anger, sadness, and persistence were rated in a goal‐blocking task in toddlerhood (T1; N = 140, 72 boys, Mage = 2.67 years, 90.7% White) and preschool (T2). Children’s self‐regulation, specifically sustained attention and engagement, was assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 65 publications
0
1
0
Order By: Relevance
“…Because mothers’ negative expressivity in toddlerhood appears to have a long-term influence on child negative affectivity, it is important for practitioners to intervene early by teaching mothers strategies to manage their negative emotions to prevent the long-term adverse impact of maternal negative expressivity on children. At the same time, because children’s negative reactivity during preschool years may also have an impact on mothers, it is equally important to provide resources and support for children to learn emotion regulation skills to help them regulate and utilize their negative emotions adaptively ( Tan and Smith, 2018 ; Tan et al, 2022 ). Researchers, practitioners, and schools may consider a family-based program that targets both the parents and the children to help them create a more optimal family emotional climate.…”
Section: Discussionmentioning
confidence: 99%
“…Because mothers’ negative expressivity in toddlerhood appears to have a long-term influence on child negative affectivity, it is important for practitioners to intervene early by teaching mothers strategies to manage their negative emotions to prevent the long-term adverse impact of maternal negative expressivity on children. At the same time, because children’s negative reactivity during preschool years may also have an impact on mothers, it is equally important to provide resources and support for children to learn emotion regulation skills to help them regulate and utilize their negative emotions adaptively ( Tan and Smith, 2018 ; Tan et al, 2022 ). Researchers, practitioners, and schools may consider a family-based program that targets both the parents and the children to help them create a more optimal family emotional climate.…”
Section: Discussionmentioning
confidence: 99%
“…In one study using this evocative task, the more 4-to 6-year-olds uttered task-relevant speech, the less they expressed nonverbal anger; in contrast, negative utterances, for example, criticizing the self ("I can't do this") or the task ("This box is stupid") were associated with more sadness (Day & Smith, 2013). However, other studies showed that anger expressed at low intensity predicted better persistence during this task, although only at age 4 years and not at younger ages (Ramsook et al, 2020;Tan et al, 2023). This suggests an adaptive function of low-level anger for persistence that develops with age.…”
Section: The Role Of Language In the Development Of Emotion Regulatio...mentioning
confidence: 96%